Story of a Master Project: the planning process of the herb garden in Szentendre - Illyés, Zsuzsanna; Gergely, Attila; Hubayné Horváth, Nóra; Módosné Bugyi, Ildikó; Nádasy, László Zoltán; Földi, Zsófia; Valánszki, István (4D Journal of Landscape Architecture and Garden Art, 2023)
Senior students of the Landscape Architecture Mastersprogramme writing their thesis at the Department of Landscape Protection and Reclamation (hereinafter: Department) conclude their education by participating in a so-called “Master Project”. The method of MasterProjects is team supervision, the supervisors being lecturers of associated courses – Thesis Project 2, Landscape Restoration, Fitting into the Landscape – and other lecturers invited based on the topic. The plan, finished in a total of eight weeks (two weeks of workshops and six weeks of study period) is typically programme-level. Creating a concept is a collaborative task, but students also make individual designs for sub-tasks. Some important characteristics of Master Projects are that they are realistic, involving real clients and contributing professionals, provide real planning tasks, and include participator elements and communication with local communities. In the autumn of 2022, the town of Szentendre reached out to the Department with a design topic that was highly compatible with Master Projects, the development of the area next to Kőhegyi Road (lot number 0181/6), in a different way from current zoning regulations. The location of the area on the settlement fringe, its zoning situation, the surrounding natural values as well as its partial designation as an ecological corridor all required careful preparation and a landscape-conservation-based approach. After preparing a site analysis, senior students writing their theses on the Department were included in the planning process. Based on the analyses and considering local restrictions and opportunities, the students designed a complex development – a half-hectare, closed herb garden and several freely accessible recreational facilities in the entry area connecting the garden with the town and transport routes. The proposal also decreases pressure on areas with high nature conservation value, with the management tasks of these valuable habitats also being appointed to the operator of the garden. Case studies provided an excellent basis for the concept of the herb garden, and based on experience, a design proposal was created that is sustainable, fits into its surroundings both visually and ecologically and fulfils economic and visitor requirements alike.
Keywords: master project; herb garden; landscape protection; landscape integration; grassland